Emerging immune functions of non-hematopoietic stromal cells - Mark Christopher Coles (Frontiers Research Topics, 2014)
The development and function of the immune system is dependent on interactions between haematopoietic cells and non-hematopoietic stromal cells. The non-hematopoietic stromal cells create the microenvironment in which the immune system operates, providing an architectural landscape for hematopoietic cell-cell interactions and molecular cues governing haematopoietic cell positioning, growth and survival. Not surprisingly, therefore, aberrant stromal cell function has recently been shown to play a key role in the development of disease pathologies associated with immune dysfunction. For example, remodelling of lymphoid tissue stroma and the development of ectopic tertiary lymphoid tissues are characteristic of many infectious and inflammatory diseases and stromal cells have a recognised role in lymphoma and tumour development and resistance to therapy. An increased understanding of the molecular basis of stromal cell differentiation and function in these varied contexts will provide new tools to promote research on stromal cell biology and immune dysfunction, and potential new targets for therapeutic intervention in diseases with a major impact on public health. The importance of stromal cells and the molecular mechanisms of stromal cell function in the regulation of immune responses have only recently been appreciated and thus represent an exciting new area in immunology.